NGTS J214358.5−380102 – NGTS discovery of the most eccentric known eclipsing M-dwarf binary system. Issue 3 (8th April 2020) - Acton, Jack S; Goad, Michael R; Raynard, Liam; Casewell, Sarah L; Jackman, James A G; Alexander, Richard D; Anderson, David R; Bayliss, Daniel; Bryant, Edward M; Burleigh, Matthew R; Belardi, Claudia; Cooke, Benjamin F; et al.
ABSTRACT: We present the discovery of NGTS J214358.5–380102, an eccentric M-dwarf binary discovered by the Next-Generation Transit Survey (NGTS). The system period of 7.618 d is greater than many known eclipsing M-dwarf binary systems. Its orbital eccentricity of 0.323^+0.0014_-0.0037 is large relative to the period and semimajor axis of the binary. Global modelling of photometry and radial velocities indicates stellar masses of M A = 0.426 ^+0.0056_-0.0049 M⊙, M B = 0.455 ^+0.0058_-0.0052 M⊙ and stellar radii R A = 0.461 ^+0.038_-0.025 R⊙, R B = 0.411 ^+0.027_-0.039 R⊙, respectively. Comparisons with stellar models for low-mass stars show that one star is consistent with model predictions whereas the other is substantially oversized. Spectral analysis of the system suggests a primary of spectral type M3V, consistent with both modelled masses and radii, and with spectral energy distribution fitting of NGTS photometry. As the most eccentric eclipsing M-dwarf binary known, NGTS J214358.5–380102 provides an interesting insight into the strength of tidal effects in the circularization of stellar orbits.